The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/su12239969
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Production, Non-Tariff Measures, and Trade Performance in RCEP Countries

Abstract: The main objective of this paper is to reinvestigate the impacts of non-tariff measures (NTMs) on bilateral exports among Regional Comprehensive Economic Partnership (RCEP) countries. The study adds to the literature in two areas. First, we calculate coverage ratios for NTMs related to specific sustainable development goals (SDGs) imposed on bilateral trade between RCEP member countries. Second, to avoid aggregation bias, the analysis covers four major sectors, namely agrifood, health, logistics, and other man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…In addition, some scholars have studied the heterogeneous effects of different trade facilitation measures on RCEP members. For instance, Zainuddin et al [8] proved that the impacts of non-tariff measures (NTM) on bilateral exports among RCEP countries are heterogeneous in different industries. Erokhin et al [9] found that there is a major imbalance between the potential value of trade among countries and the actual advantages of RCEP economies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some scholars have studied the heterogeneous effects of different trade facilitation measures on RCEP members. For instance, Zainuddin et al [8] proved that the impacts of non-tariff measures (NTM) on bilateral exports among RCEP countries are heterogeneous in different industries. Erokhin et al [9] found that there is a major imbalance between the potential value of trade among countries and the actual advantages of RCEP economies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, implementing NTMs with the TBT type positively affected Indonesia's natural rubber export in various destination countries (Virginia & Novianti, 2020). On the other hand, research on NTMs and the export performance of RCEP countries unveiled that the implementation of NTMs by importing countries reduced the export performance of the health sector (Zainuddin, Sarmidi, & Khalid, 2020). It is supported by a study concerning NTMs and the export performance of Indonesia's fishery commodities, uncovering that NTMs harmed the export performance of these commodities (Permata & Handoyo, 2019).…”
Section: And Rural Development Researchmentioning
confidence: 98%
“…Furthermore, the trade value for Indonesia's TSNR subject to NTMs in an importing country can be seen from the coverage ratio. The coverage ratio can demonstrate the reach of NTMs and their importance for imported goods (Zainuddin et al, 2020). The coverage ratio was examined using the following formula (Disdier & Fugazza, 2019).…”
Section: Rer=ner× Cpi I Cpi Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…As globalization proceeds rapidly and in a much more complex way, multilateral free trade agreements, such as the Regional Comprehensive Economic Partnership (RCEP), have been pursued for economic transformation breakthroughs. Related to the issue of sustainability, recent works highlight, among others, the dynamic and diverse economic aspects in RCEP countries (e.g., References [7,8]).…”
Section: Introductionmentioning
confidence: 99%